COMPARATIVE ANALYSIS OF EXPERIENCE OF GEORGIA AND UKRAINE IN IMPLEMENTATION OF MEDIATION IN COMMERCIAL DISPUTES - Francuz Anatolij; Viktoriia Polishchuk (Legal Bulletin, 2021)
This article is devoted to the analysis of the practical experience of mediation application in commercial disputes. A comparative analysis of the historical development of mediation in Georgia and Ukraine has been made. In the past in Georgia, mediators were found to be individuals, who enjoyed authority and trust among the members of society and who knew laws very well. In Ukraine, mediation has developed as a part of negotiations between the disputing parties. It is determined that current mediation in Georgia and Ukraine is developing in different ways. The starting point of the mediation development in Georgia can be considered a creation of a mediation clinic at the university. Thereafter, an institution that was focused on social dialogue was created in Georgia in 2008. Further development of mediation in Georgia was accompanied by the introduction of pilot projects and the active development of the training system for the new profession, namely a mediator. The result of pilot projects in Georgia was the adoption of amendments to the Civil Procedure Code, which established two forms of mediation. Mediation has become a must in family disputes and in settling disputes between neighbours. For other types of disputes, including commercial disputes, mediation was a recommendation. It was researched that financial incentives and accountability have been also applied to encour- age mediation in Georgia. For parties, who have used mediation before applying to the court but have not reached an agreement, a lower court fee is set. If the parties have waived the obligatory mediation, the defaulting party shall pay a fine. Georgian law also stipulates the possibility of enforcement of a decision made in the mediation process if one of the parties fails to comply with it. The author analysed that the draft law on mediation in Georgia will stimulate the state and all its bodies and businesses to actively use mediation in any disputes. In Ukraine, the development of mediation began in the 1990s. It is researched that Ukraine and Georgia have a similar start in the introduction of mediation into the legal system. An authority that is engaged in social dialogue has also been set up in Ukraine. However, in the absence of effort consolidation of all stakeholders in the legal definition of the mediation process in Ukraine, paths of mediation development in Ukraine and Georgia had split. It is concluded that the criterion of the success in implementation of mediation in legal terms is the need to introduce mediation disciplines in higher education institutions and to carry out educational work among the population on the effectiveness of this method of dispute resolution.